THE AESTHETIC FUNCTION OF THE GROTESQUE IN THE FIGURATIVE CONCEPT OF V. NABOKOV - N. Riaguzova, Liudmila; V. Cherevko, Galina; Yan, Li; Xiaojie, Zhao (Revista Inclusiones, 2021)
This article discusses the aesthetic functions of the grotesque in the work of V. Nabokov as a highly artistic and metaphysical meaning in a comparative view; consideration is carried out from the provisions of philosophical, structural and general chemical scientific methods. The importance and relevance of the study of such a complex technique helps to establish a connection in the work of the author of the "subject" grotesque and grotesque consciousness. The disclosure of semantic methods allows you to view in them the actualization of the motives of the absurdity of existence, the combination in author-individual comparisons of zoomorphic and anthropomorphic series. In addition, to present the historical connection between the methods of modeling "other" reality and the description of characters with a distorted mind in the work of Nabokov-Sirin and classics of fiction. Nabokov considered naming literary methods one of the important compositional elements of artistic analysis, therefore, our approach corresponds to the object of cognition. The study highlights some of the fundamental details of grotesque expressiveness in the author's prose in the critical and artistic styles of depicting reality. In particular, both from the position of postmodern game poetics, on the one hand, and subjective-mythological ideas - on the other. The task of the article is to show how the originality of the meta-description of reception in the author goes into the definition of the canons of grotesque unity and the comparison of picturesque nature with the aesthetic functions of literature as a type of art. This meaning shows how V. Nabokov's terminological and conceptual system with its features of ambivalence and distortion (concepts of "pattern," "arabesque," "prism") is consistent with the artistic nature of the grotesque.